ANÁLISE COMPARATIVA DA UTILIZAÇÃO DO MODELO TRADICIONAL (WATERFALL) DE DESENVOLVIMENTO DE PROJETOS E O MODELO ÁGIL (AGILE) EM FÁBRICAS DE SOFTWARE - Rivas, Mario Augusto; FIAP (2014)
Over the last few years Agile methodologies usage by the information technology industry considerably increased, due to the high productivity and quality of the products created, among other factors. In this scenario, software factories that traditionally applied waterfall methodology for development initiatives are starting to use Agile frameworks as Scrum or XP. This article presents a comparative analysis between the traditional model (waterfall) and the Agile model on the software factories context, describing the main topics that must considered in order appraise a proper methodology, through a comparative matrix.